Prominent Daytime TEC Enhancements Under the Quiescent Condition of January 2017 - Fuqing Huang; Jiuhou Lei; Ruilong Zhang; Na Li; Shengyang Gu; You Yu; Libo Liu; Charles Owolabi; Baiqi Ning; Guozhu Li; Jiahao Zhong; Tong Dang; et al. (Geophysical Research Letters)
Abstract It is well known that the ionospheric electron densities in the F‐region usually undergo day‐to‐day variability with the magnitude of ~20–35%, associated with the solar as well as geomagnetic activities and the meteorological forcing from the lower atmosphere. In this study, we reported remarkable enhancements in the total electron content (TEC) from the Beidou geostationary (GEO) satellites during the quiescent geophysical condition of January 2017 prior to the arrival of the sudden stratosphere warming (SSW). The daytime TEC around the equatorial ionization anomaly region increased by 75–160% and lasted for several days. The equatorial electrojet and Sq current in the ionospheric E‐region at low and middle latitudes showed the corresponding increase during the TEC enhancement interval. The possible contributions from the variations of solar EUV flux and geomagnetic activity are ruled out. Our further analysis showed that the diurnal tides in the temperature from Sounding of the Atmosphere using Broadband Emission Radiometry and the solar and lunar semidiurnal tides of neutral winds from two radars over China became strong during this period of interest. These results suggest that the lower atmospheric tidal forcing could contribute to the great and long‐duration TEC enhancement in the ionosphere even though the SSW had not happened yet.